2020
DOI: 10.3791/61606
|View full text |Cite
|
Sign up to set email alerts
|

A Biomimetic Model for Liver Cancer to Study Tumor-Stroma Interactions in a 3D Environment with Tunable Bio-Physical Properties

Abstract: Hepatocellular carcinoma (HCC) is a primary liver tumor developing in the wake of chronic liver disease. Chronic liver disease and inflammation leads to a fibrotic environment actively supporting and driving hepatocarcinogenesis. Insight into hepatocarcinogenesis in terms of the interplay between the tumor stroma microenvironment and tumor cells is thus of considerable importance. Three-dimensional (3D) cell culture models are proposed as the missing link between current in vitro 2D cell culture models and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 3 publications
0
17
0
Order By: Relevance
“…Cell viability was evaluated after drug treatment for 24, 48 or 72 h by a resazurin reduction assay, as previously described [ 31 ]. A 1% solution of resazurin sodium salt (Sigma-Aldrich) was prepared according to manufacturer’s recommendation and diluted 1/80 in CCM SM .…”
Section: Methodsmentioning
confidence: 99%
“…Cell viability was evaluated after drug treatment for 24, 48 or 72 h by a resazurin reduction assay, as previously described [ 31 ]. A 1% solution of resazurin sodium salt (Sigma-Aldrich) was prepared according to manufacturer’s recommendation and diluted 1/80 in CCM SM .…”
Section: Methodsmentioning
confidence: 99%
“…The HCC-cell lines (HepG2, ATCC HB-8065 and Huh7, kind gift from Dilruba Ahmed, Karolinska Institute, Sweden) and the human hepatic stellate cell-line LX2 (SCC064, Sigma-Aldrich, Darmstadt, Germany) were cultured at 37°C with 5% CO 2 in high glucose Dulbecco modified eagle medium, GlutaMAX supplemented (DMEM) (31066047, ThermoFisher Scientific, Stockholm, Sweden) supplemented with 1% antibiotic antimycotic solution (A5955-100ML, Sigma-Aldrich, Darmstadt, Germany) followed by 10% and 2% fetal bovine serum (FBS) (10270106, ThermoFisher Scientific, Stockholm, Sweden) for the HCC cell lines and LX2 cell line, respectively ( Calitz et al, 2020 ). No FBS was used during starvation and stimulation with growth factors.…”
Section: Methodsmentioning
confidence: 99%
“…For transwell co-culturing experiments, cells were grown on 12-well Corning Costar Transwell plates (3460, Sigma-Aldrich, Darmstadt, Germany) with 0.4 μm-pore polyester membrane, allowing the exchange of soluble factors, but preventing direct cell contact ( Calitz et al, 2020 ). Cells were detached using 0.05% trypsin-EDTA (15400054, ThermoFisher Scientific, Stockholm, Sweden), re-suspended in growth medium and seeded at a density of 1.0 × 10 5 cells per well and 4.0 × 10 4 cells per insert.…”
Section: Methodsmentioning
confidence: 99%
“…The cirrhotic liver is characterized by a severe inflammatory reaction and an excessive deposition of extracellular matrix, which actively contributes to the progression of HCC [ 45 , 46 ]. Several studies have suggested that therapeutic response relies partly on extrinsic mechanisms provided by the crosstalk between tumour cells and components of the tumour microenvironment ( Figure 3 ).…”
Section: The Role Of the Tumour Microenvironmentmentioning
confidence: 99%